2008
DOI: 10.1037/0022-3514.95.2.274
|View full text |Cite
|
Sign up to set email alerts
|

Self-handicapping, excuse making, and counterfactual thinking: Consequences for self-esteem and future motivation.

Abstract: Researchers interested in counterfactual thinking have often found that upward counterfactual thoughts lead to increased motivation to improve in the future, although at the cost of increased negative affect. The present studies suggest that because upward counterfactual thoughts indicate reasons for a poor performance, they can also serve as excuses. In this case, upward counterfactual thoughts should result in more positive self-esteem and reduced future motivation. Five studies demonstrated these effects in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
72
1
9

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(94 citation statements)
references
References 95 publications
5
72
1
9
Order By: Relevance
“…Conversely, regarding problems with time management, women reported a more frequent use of these strategies than their male peers. These results do not agree with those of previous studies which found that men typically exhibit behavioral self-handicaps more often than women (Hirt et al, 2000;Hirt et al, 2003;McCrea, 2008). However, due to the small sample of male students, it is essential that further investigations be conducted with an equal number of participants from both genders.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Conversely, regarding problems with time management, women reported a more frequent use of these strategies than their male peers. These results do not agree with those of previous studies which found that men typically exhibit behavioral self-handicaps more often than women (Hirt et al, 2000;Hirt et al, 2003;McCrea, 2008). However, due to the small sample of male students, it is essential that further investigations be conducted with an equal number of participants from both genders.…”
Section: Discussioncontrasting
confidence: 81%
“…The studies have investigated the relationship between the use of these strategies and motivation (Graham, Tisher, Ainley, & Kennedy, 2008;Hirt, McCrea, & Boris, 2003;McCrea, 2008), self-esteem (Seli, Dembo, & Crocker, 2009), performance (Martin et al, 2001;McCrea et al, 2008;Schraw et al, 2007;Smith et al, 2009) and emotions (Alter & Forgas, 2007;Coudevyle, Martin Ginis, Famose, & Gernigon, 2009;Hendrix & Hirt, 2009). Generally, the use of self-handicapping strategies is associated with low self-esteem, reports of psychological symptoms (such as stress and anxiety), poor academic performance and lack of organization and academic goals (Hendrix & Hirt, 2009;Martin et al, 2001;McCrea, 2008;Schwinger & Stiensmeier-Pelster, 2011). Regarding the differences between genders, the data indicate that women evaluate self-handicapping behaviors more negatively than men and use these strategies less often (Hirt et al, 2003;Hirt, McCrea, & Kimble, 2000;McCrea et al, 2008).…”
mentioning
confidence: 99%
“…Taken together, these and other results (e.g., McCrea, 2008;Petrocelli & Harris, 2011), which were obtained for different tasks and conditions, seriously challenge the preparatory hypothesis, suggesting that the primary function of counterfactuals may be other than the preparatory one.…”
mentioning
confidence: 62%
“…When tasks involve such sessions, individuals who have experienced a failure generate counterfactuals that do focus on their preparatory effort. For example, McCrea (2008) found that undergraduates who had failed an exam and had reported a lack of study effort tended to produce counterfactual thoughts about studying (e.g., "If I had studied more I could have done better").…”
Section: Discussionmentioning
confidence: 99%
“…For example, if there 570 is conflict between two athletes then a coach might use each athlete's counterfactuals using 571 reflective practice to come up with a management strategy to overcome the issue. Also, 572 counterfactuals could be used to gain perspective on these goals and protect an athlete's self-573 esteem following failure (McCrea, 2008). Beyond the scope of elite athletes, individuals who 574 participate in performance related activities (e.g., business, sport & exercise practitioners, 575 health services) would benefit from lessons learned from elite athletes to understand and 576 suitably utilize counterfactuals to facilitate cognitive, emotional and behavioral change to 577 enhance their practice.…”
Section: We Go To Coach Feedback and Have A Chat Then We Go To Cool Dmentioning
confidence: 99%